Eco-architecture - Espejo, Roman (Farmington Hills, MI : Greenhaven Press, 2013)
This volume explores the topics relating to sustainable architecture, a general term that describes environmentally conscious design techniques in the field of architecture, by presenting varied expert opinions that examine many of the different aspects that comprise these issues. The viewpoints are selected from a wide range of highly respected and often hard-to-find sources and publications. Allows the reader to attain the higher-level critical thinking and reading skills that are essential in a culture of diverse and contradictory opinions.
Chapter 1. Is eco-architecture beneficial? Eco-architecture has many benefits / Alanna Stang and Christopher Hawthorne -- Eco-architecture is economically beneficial / DNA: Daily News & Analysis -- Eco-architecture is economically risky / Teresa Burney -- The LEED building standards protect human health / Shannon D. Sentman -- The LEED building standards do not protect human health / John Wargo -- Chapter 2. How does eco-architecture impact the environment? Eco-architecture benefits the environment / Secretariat of the Commission for Environment Cooperation (CEC) -- Eco-architecture does not benefit the environment / Jane Powell -- Large houses can be eco-friendly / Blair Kamin -- Large houses cannot be eco-friendly / Jason F. McLennan -- Urban sprawl can be beneficial / Robert Bruegmann -- Urban sprawl is not beneficial / Pamela Blais -- Chapter 3. How is eco-architecture being implemented? More college campuses are building green / Peter W. Bardaglio -- More school campuses are building green / Jonathan Hiskes -- Hospitals go green / Karen Sandrick -- False claims of green building practices create confusion / Jay B. Freedman -- Current green building certification is not enough / Jason F. McLennan, as told to Jonathan Hiskes -- Chapter 4. How can eco-architecture be encouraged in the future? Stylish design will encourage more people to opt for eco-architecture / Inken Herzig -- Green building blues: is "well-designed green architecture" an oxymoron? / Kriston Capps -- The LEED rating system helps create greener buildings / Helen Kessler -- The LEED rating system is not effective / Anya Kamenetz -- Some homeowners associations will take eco-friendly practices into consideration / T.Q. Jones -- Obtaining homeowners associations' approval of eco-friendly practices is difficult / J. Roger Wood -- Organizations to contact.
Includes bibliographical references and index.
Keywords: SUSTAINABLE ARCHITECTURE; SUSTAINABLE BUILDINGS